ANALISIS MANAJEMEN OLAHARAGA ASOSIASI FUTSAL KABUPATEN BONE - Elfian Elfian; Sarifin G; Wahyudin Wahyudin (Program Studi Ilmu Keolahragaan FIK UNM, 2023)
This study is a descriptive study that aims to present an overview of the implementation of sports management in the Asosiasi Futsal Kabupaten Bone. This study uses a combination method, namely, qualitative and quantitative (mix method). The variable used in this study is a single variable, namely sports management and consists of four sub-variables namely, planning, organizing, actuaing, and controling. The population of this study were all parties under the auspices of the Asosiasi Futsal Kabupaten Bone which consisted of 25 administrators, 2 coaches, and 14 athletes. As for the sample, there are 9 administrators, 2 coaches and 14 athletes. The research data was obtained using a survey method which was then analyzed descriptively to get an overview of the data including the lowest score, the highest score, the data including the mean, standard deviation and variance. Based on the results of research and data analysis, it can be concluded that. The sport management condition of the Asosiasi Futsal Kabupaten Bone is in the strong category.